Factors controlling margin instability during the Plio-Quaternary in the Gela Basin (Strait of Sicily, Mediterranean Sea). (January 2021) - Gauchery, Tugdual; Rovere, Marzia; Pellegrini, Claudio; Cattaneo, Antonio; Campiani, Elisabetta; Trincardi, Fabio
Abstract: This study presents novel findings on the Pliocene and Quaternary evolution of the Gela Basin (Strait of Sicily, Mediterranean Sea), an area recording the interaction between tectonics, climate change at Milankovitch and sub-Milankovitch timescales, and dynamic water masses exchange between the eastern and western Mediterranean Sea. The calibration of seismic profiles with exploration boreholes allowed for the refining of the chronostratigraphic framework of the Gela Basin and highlighted the main phases of margin growth. Since the Pliocene, the margin has recorded the deposition of 100 m high shelf-edge clinothems, accompanied by sediment drifts on the slope and mass-transport deposits (MTDs), possibly triggered by seismic activity. Through the Plio-Quaternary the locus of deposition of sediment drifts migrated upslope due to a progressive shift of bottom currents. After the Middle Pleistocene Transition (MPT) the margin experienced an accelerated outbuilding with the deposition of a 700 m thick succession in only 0.8 Myr. At this time, a marked change in sedimentary architecture reflects the growth of shelf-edge clinothems and associated MTDs on the slope, and the spreading of contourite deposits over a broader and generally shallower area. Sediment flux to the basin and the intensity of bottom currents appear both paced at 100 kyr eccentricity orbital cycles. The growth of bottom current deposits on a large portion of the upper slope and outer shelf likely reflects constraints to the bottom current flow by the margin morphology, inherited from Miocene and Pliocene tectonics. Overall, a combination of long-term tectonic activity, climate change and shifts in oceanographic regime resulted in a complex along-strike variability of the margin morphology and stratigraphic architecture and affected where and when MTDs were emplaced. These conclusions show how climate cyclicity influence sediment supply which combined with margin morphology can promote slope instability in continental margins. Highlights: Evolution of the Gela Basin (Mediterranean Sea) during Plio-Quaternary investigated. The outbuilding of the margin changed after the Middle Pleistocene Transition. Contourite deposits play a key role in margin destabilization. Clinothems and associated submarine landslides are paced at Milankovitch cyclicity. Erosional unconformities act as glide planes for submarine landslides.